Pengaruh Promosi Media Sosial dan Kualitas Produk Terhadap Keputusan Pembelian Pada Usaha Kuliner Macinos - Febriana, Laras Sastri Amelia; Ratnaningtyas, Heny; Dewi, Triana Rosalina (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan Digital, 2026)
ABSTRACT This study aims to analyze the influence of social media promotion and product quality on purchasing decisions at Macinos Culinary Business in Bintaro, South Tangerang. This research employed a quantitative, data were collected through a questionnaire distributed to consumers selected as research respondents using a five-point Likert scale. The data were analyzed using multiple linear regression with the assistance of SPSS software after the research instrument had met the validity and reliability requirements. The findings indicate that social media promotion does not have a significant effect on purchasing decisions, whereas product quality has a positive and significant effect on purchasing decisions. Simultaneously, social media promotion and product quality have a significant effect on purchasing decisions, indicating that both variables contribute to explaining variations in consumers' purchasing decisions. This study concludes that product quality is a more dominant factor influencing purchasing decisions than social media promotion. Therefore, business owners are encouraged to maintain and continuously improve product quality while optimizing social media promotion through more engaging, interactive, and consumer-oriented content to enhance marketing effectiveness and stimulate consumers' purchasing decisions. Keywords: social media promotion, product quality, purchasing decisions